Averrhoa bilimbi L. Fruit Extract as a Potential Alternative Root Canal Irrigant: An In Vitro Evaluation against Staphylococcus aureus - Daryono; Member Reni Purba; Dinda Rizky Aulia (Open Access Indonesian Journal of Medical Reviews, 2025)
Staphylococcus aureus is a prevalent bacterium in root canal infections, contributing to treatment failure due to its persistence within dentinal tubules. Conventional root canal irrigants like sodium hypochlorite (NaOCl), while effective, can have cytotoxic effects on host tissues. Averrhoa bilimbi L. fruit, traditionally used for medicinal purposes, has shown promising antibacterial activity. This study aimed to evaluate the in vitro antibacterial effectiveness of A. bilimbi fruit extract against S. aureus and compare it with NaOCl. A. bilimbi fruits were extracted using ethanol. The antibacterial activity of the extract at varying concentrations (70%, 60%, and 50%) was assessed against S. aureus using the disc diffusion method. NaOCl (2.5%) served as the positive control, and dimethyl sulfoxide (DMSO) as the negative control. The diameter of inhibition zones was measured and statistically analyzed using Kruskal-Wallis and Mann-Whitney tests. A. bilimbi fruit extract demonstrated significant antibacterial activity against S. aureus at all tested concentrations. The diameter of inhibition zones increased with higher extract concentrations (70% > 60% > 50%). While NaOCl exhibited the largest inhibition zone, A. bilimbi extract showed comparable efficacy to NaOCl, and significantly greater efficacy than DMSO. A. bilimbi fruit extract exhibits promising antibacterial activity against S. aureus in vitro. Its efficacy, comparable to NaOCl at higher concentrations, suggests its potential as an alternative root canal irrigant. Further studies are warranted to explore its clinical application in endodontic treatment.